2009
DOI: 10.1007/s12328-009-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy case of acute liver failure due to scrub typhus

Abstract: Scrub typhus (Tsutsugamushi disease) is an acute febrile disease caused by infection with Orientia tsutsugamushi transmitted by mites. Although patients with scrub typhus commonly display mild liver injury, few die of acute liver failure. We describe herein an autopsy case of acute liver failure due to scrub typhus, which was complicated by disseminated intravascular coagulation and showed rapid progression of liver injury just before death. Histopathological findings revealed submassive hepatocellular necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In a retrospective short report by Hu et al [5], from Taiwan, 90% of the patients had a significant surge in SGOT, SGPT, and gamma-glutamyl transferase although alkaline phosphatase was found to be raised in 35-40% of the participants. In agreement with our diagnosis, Shioi et al [8] reported an autopsy of a scrub typhus patient who drowned in virtue of acute liver failure. Not surprisingly, findings were of submassive hepatic necrosis, infiltrates in the Glisson's capsule, and sporadic fibrin thrombi in the sinusoids backing disseminated intravascular coagulation.…”
Section: Discussionsupporting
confidence: 90%
“…In a retrospective short report by Hu et al [5], from Taiwan, 90% of the patients had a significant surge in SGOT, SGPT, and gamma-glutamyl transferase although alkaline phosphatase was found to be raised in 35-40% of the participants. In agreement with our diagnosis, Shioi et al [8] reported an autopsy of a scrub typhus patient who drowned in virtue of acute liver failure. Not surprisingly, findings were of submassive hepatic necrosis, infiltrates in the Glisson's capsule, and sporadic fibrin thrombi in the sinusoids backing disseminated intravascular coagulation.…”
Section: Discussionsupporting
confidence: 90%
“…Scrub typhus has been reported to be an important infectious cause of acute liver failure in India, along with dengue, viral hepatitis, malaria and amoebic liver abscess [16]. Pathologic examination of the liver of a 73-year-old woman with acute liver failure in Japan displayed necrosis and fatty degeneration of hepatocytes, inflammatory infiltrate of lymphocytes, macrophages and plasma cells in the Glisson's capsule, and presence of fibrin thrombi in the hepatic sinusoids, suggesting microvascular injury due to DIC as the mechanism of fulminant liver failure [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported in neonates with scrub typhus [11]. Histopathologic examination of the liver on autopsy of a patient with acute liver failure secondary to scrub typhus revealed necrosis of hepatocytes, inflammatory infiltrate in hepatic capsule and fibrin thrombi in the sinusoids [12]. These findings were suggestive of DIC as the possible mechanism.…”
Section: Discussionmentioning
confidence: 65%